Activation of kaolin with minimum solvent consumption by microwave heating. (December 2014) - Al Bakain, R. Z.; Al-Degs, Y. S.; Issa, A. A.; Abdul Jawad, S.; Abu Safieh, K. A.; Al-Ghouti, M. A.
Abstract: A kaolin clay was activated with 1.0 M H2 SO4 solution at minimum liquid to solid ratio (L/S) using microwave heating. The optimum experimental conditions for activation were L/S ratio 3.0 mL 1 M H2SO4 per gram kaolin, microwave input power 500–600 W, and heating time 5–10 min. Activation at L/S < 3.0 mL/g using 1.0 M H2 SO4 was not efficient, indicating the influence of solvent for absorbing microwaves more intensively and thus improving activation. Significant physicochemical changes were observed by the proposed procedure with smaller volumes of activator compared to the conventional heating method. Microwave input power and heating time have a strong influence on the quality of the final material; activation at high input power (>700 W) and longer heating times (>10 min.) are not recommended since they cause dissolution of kaolinite structure. Microwave-heated kaolin manifested better adsorption for tartrazine dye due to improvements in textural and chemical properties of kaolinite. Moreover, irradiation of used kaolinite has significantly improved dye desorption, increasing the importance of microwaves in regeneration/recycling studies. Detailed dielectric measurements of kaolin-acid mixtures recorded at frequencies much lower than 2.45 GHz revealed that absorption of radiation is highly dependent on the activator solution in the mixture. For 3.0 mL/g mixtures, high dielectric constant ε' 5223, dielectric loss factor ε" 5083, tangent loss tan d 1.30, penetration depth dp 0.57 cm at (10 3 Hz), and AC-conductivity σ 0.032 Om –1 were determined at 105 Hz. Filling the pores of kaolin by acid solution increased the microwave absorption and hence de-alumination of kaolinite.